Antimicrobial susceptibility of uropathogens isolated from Cambodian children. (2nd April 2016) - Moore, Catrin E.; Sona, Soeng; Poda, Sar; Putchhat, Hor; Kumar, Varun; Sopheary, Sun; Stoesser, Nicole; Bousfield, Rachel; Day, Nicholas; Parry, Christopher M.
Abstract : Background: Bacterial resistance to commonly used antimicrobials is an increasing problem in Asia but information concerning the antimicrobial susceptibility of bacteria causing urinary tract infections (UTIs) in children is limited. Methods: This was a 5-year retrospective study of children with suspected UTI attending a paediatric hospital in north-west Cambodia. Urines with a positive culture containing a single organism with a count of >10 5 colony-forming units (CFU)/ml were considered diagnostic of infection. The organism was identified and the resistance pattern (using CLSI guidelines) and presence of an extended-spectrum β-lactamase (ESBL) phenotype was determined. Results: In total, there were 217 episodes of infection, 210 (97%) with Gram-negative bacteria. Escherichia coli was the most common infecting isolate with high levels of resistance to most oral antibiotics, except nitrofurantoin. Nearly half of the E. coli (44%) were extended-spectrum cephalosporin (ESC)-resistant with the proportion increasing significantly over the 5-year period. ESC-resistant E. coli were more likely to be multi-drug-resistant and 91% demonstrated an ESBL phenotype. Conclusion: The data highlight the importance of microbiological surveillance of UTIs in children, particularly in areas where there are known to be multiply resistant organisms.